The paths of Creative Insubordination: a brief theoretical debate - Silveira, Tiago Cardoso (2021)
This work is part of a doctoral thesis and aims to present the theme Creative Insubordination, the paths followed since its genesis, as well as the terms Responsible Subversion and Positive Deviance that allude to the idea of ​​insubordinately creative actions. It is a research with a qualitative approach and regarding the technical procedures it fits as a bibliographic research. Thus, the next topic is divided into four subtopics which are: Creative Insubordination, responsible subversion, positive deviation and creative insubordination in the Brazilian context of Mathematics Education. It was found that the term creative insubordination was used in the late 1970s and early 1980s in the field of Ethnography, but it was Rochelle Gutierrez, an American educator, who was the first to use the concept of creative insubordination in the field of Education Math. In Brazil, educators Beatriz Silva D'Ambrosio and Celi Espasandin Lopes were the first to study and disseminate this term in the Brazilian context and associate it as a synonym for responsible subversion both in the practice of teachers and researchers. term the concepts of ethics, solidarity and social justice.